Resistência antimicrobiana nas infecções primárias de corrente sanguínea na pandemia da Covid-19, o que mudou em um hospital do Nordeste do Brasil? - Xavier, Jonathan da Silva (2024)
Covid-19 is an acute respiratory infection caused by SARS-CoV-2, a betacoronavirus discovered in the city of Wuhan, China, in December 2019. The high transmissibility of this infectious pathology, the extent of the involvement and severity of the cases resulted in the largest pandemic seen in 100 years. During the Covid-19 pandemic, the long periods of hospitalization, exacerbated use of antimicrobials and the difficulty in following established protocols may have modified the profile of microorganisms, the resistance pattern and the clinical outcome of patients. This study aims to investigate changes in the profile of bacterial and fungal species, as well as antibacterial resistance in primary bloodstream infections (BSI), during the Covid-19 pandemic (2020 to 2021) in patients admitted to the Intensive Care Unit (ICU) of a reference hospital for the disease in Fortaleza. This is a cross-sectional and analytical study carried out by reviewing medical records, ICU laboratory records and notifications of Healthcare-Related Infections (HAIs) from the Hospital Infection Control Service (HICS) from 2018 to 2021. The data obtained was compared between the two periods: the pre-pandemic period (2018-2019) and the pandemic period (2020-2021). Information on morbidity, length of stay and mortality in the two periods was also investigated. 136 patients were included, 94 admitted during the pandemic and 42 hospitalized in the pre-pandemic period. The majority of patients were male, with a lower average age in the pandemic period group (73 years [standard deviation - SD: 15,2] vs 64 years [SD: 15,1]). A total of 94 bacteria were isolated (pre-pandemic 27; pandemic 67), with Pseudomonas aeruginosa being more frequent in the pre-pandemic and Klebsiella pneumoniae in the pandemic. As for the 42 fungi isolated (pre-pandemic 13; pandemic 29), the most frequent in the pre-pandemic was Candida albicans and in the pandemic Candida tropicalis. Of all the bacterial isolates, 94.68% showed resistance to at least one antibiotic, with an average resistance of 6.3 antibiotics (SD= 4; 95%CI= 5.4 - 7.1). In the pre-pandemic the average amount of resistance was 4.8 (SD= 3.4) antibiotics per bacterium, while in the pandemic this average rose to 7 (SD= 4.1) antibiotics. There was a difference in bacterial resistance by class of antibiotic: in the pre-pandemic the most frequent classes were: penicillins (96%, n=28) and 2nd generation cephalosporins (57.1%, n=28), while in the pandemic they were: carbapenems (115.5%, n=65) and 3rd generation cephalosporins (86.1%, n=65). There was no statistical difference between the number of central venous catheter (CVC) insertions in the patients (p=0.95). Patients with some comorbidity had a higher frequency of death (24%), but without statistical significance. There were no statistical differences in terms of length of stay in the ICU, but patients admitted due to Covid-19 died more quickly when we associated this outcome with length of stay (p=0.005). The clinical outcome death occurred more frequently during the pandemic (p= 0.014), however, there was no association between mortality and the isolated agent, despite the fact that deaths occurred 16% more often in patients infected with bacteria (PR=1.16). In conclusion, the differences in the microbial profile, antibiotic resistance and clinical outcome of the patients were noticeable.